Studies on The Interaction of Gemini Surfactant With Anionic Azo Dyes by Absorption Spectroscopy - Ni, R.J.; Huang, Y.; Yao, C. (Asian Journal of Chemistry, 2010)
The interactions of two anionic azo dyes, methyl orange and methyl red, with a kind of gemini surfactant in aqueous solution have investigated by means of UV-Vis spectroscopy. It was observed that the aggregation of surfactant and dye takes place at surfactant concentrations far below the critical micelle concentration of the surfactant. Aggregations with anionic dyes were reflected by hypsochromic shifts with a decrease in the intensity of absorption band. The results show the absorption spectrum of methyl orange at 510 nm for acidic form gradually decreased whereas the absorption at about 430 nm increased with the increasing of pH. For methyl red, bathochromic shifts take place from 525 to 420 nm with the increasing pH.